2015
DOI: 10.1186/s12950-015-0085-0
|View full text |Cite
|
Sign up to set email alerts
|

Nur77 deficiency leads to systemic inflammation in elderly mice

Abstract: Background Nur77, an orphan member of the nuclear receptor superfamily, has been implicated in the regulation of inflammation. However, the in vivo function of Nur77 remains largely unexplored. In the current study, we investigated the role of Nur77 in inflammation and immunity in mice.FindingsWe found that elderly 8-month-old Nur77-deficient mice (Nur77−/−) developed systemic inflammation. Compared to wild-type (WT) mice (Nur77+/+), Nur77−/− mice showed splenomegaly, severe infiltration of inflammatory cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 25 publications
0
30
1
Order By: Relevance
“…Recent studies have also shown that Nur77‐deficient mice are more susceptible to endotoxic shock . The elderly mice lacking Nur77 had severe systemic inflammation and elicited pro‐inflammatory M1 macrophages . In this study, we investigated the physiological relevance of Nur77 in IBD pathogenesis.…”
Section: Discussionmentioning
confidence: 97%
“…Recent studies have also shown that Nur77‐deficient mice are more susceptible to endotoxic shock . The elderly mice lacking Nur77 had severe systemic inflammation and elicited pro‐inflammatory M1 macrophages . In this study, we investigated the physiological relevance of Nur77 in IBD pathogenesis.…”
Section: Discussionmentioning
confidence: 97%
“…Lung tissues were collected for metastatic foci evaluation and standard histopathologic study. The details have been described recently (36)(37)(38). All animal experiments were approved by the Animal Care and Use Committee of Soochow University (Suzhou, Jiangsu, China).…”
Section: Xenograftsmentioning
confidence: 99%
“…The biological functions of NR4A1 are complex and diverse and are often diametrically opposed. For instance, in the context of inflammation, NR4A1 deficiency leads to systemic inflammation in elderly mice, aggravates experimental colitis and hepatitis, and polarizes macrophages toward a pro‐inflammatory M1 phenotype, whereas retroviral overexpression of NR4A1 in macrophages activates the NF‐κB inflammatory pathway …”
Section: Introductionmentioning
confidence: 99%